2003
DOI: 10.1093/ajcn/78.4.711
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled crossover study of the effect of a highly β-glucan–enriched barley on cardiovascular disease risk factors in mildly hypercholesterolemic men

Abstract: The effect of beta-glucan-enriched barley on lipid profile was highly variable between subjects, and there was no evidence of a clinically significant improvement in CVD risk across this group of mildly hyperlipidemic men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(114 citation statements)
references
References 62 publications
3
106
1
4
Order By: Relevance
“…Various glucan modifications and substances with different concentrations of poorly defined -glucans are routinely tested (Davidson et al, 1991;Kahlon et al, 1993). This is addition to the fact that some of these glucans (Keogh et al, 2003) had previously been found to be inactive (Vetvicka and Vetvickova 2007).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Various glucan modifications and substances with different concentrations of poorly defined -glucans are routinely tested (Davidson et al, 1991;Kahlon et al, 1993). This is addition to the fact that some of these glucans (Keogh et al, 2003) had previously been found to be inactive (Vetvicka and Vetvickova 2007).…”
Section: Discussionmentioning
confidence: 90%
“…These glucans were shown to reduce serum cholesterol in both hypercholesterolemic animals (Fadel et al, 1987;Kahlon et al, 1993;Delaney et al, 2003) and humans (Queenan et al, 2007). However, some studies found no such effects (Keogh et al, 2003). These studies held the problem of routinely using poorly defined glucans thus making interpretation of the results extremely difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of the barley beverages were less pronounced. Keogh et al (2003) also reported a poor cholesterol-lowering effect of a daily supplement of 10 g of barley b-glucans compared to a control diet and conclude that the lack of effect may be a consequence of structural changes in b-glucan that result from food processing or storage of the barley products. Furthermore, in this study there was a greater variability in lipid profile than predicted between and within subjects that could have masked small improvements in total-cholesterol.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies (Anderson et al, 1990;Hallfrisch & Behall, 2000;Keogh et al, 2003) have shown that the delayed glucose absorption probably is due to the high viscosity of b-glucans. Bourdon et al (1999) demonstrated that there was no significant difference in the glucose response between a meal with enriched barley pasta (5 g of b-glucans) and wheat pasta, but the insulin response differed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation